Evaluation of the electromyography test for the analysis of the aerobic-anaerobic transition in elite cyclists during incremental exercise - Latasa, I.; Cordova, A.; Quintana-Orti, G.; Lavilla-Oiz, A.; Navallas, J.; Rodriguez-Falces, J. (Applied Sciences, 2018)
(1) Background: The aim of this study was to investigate the validity and reliability of surface electromyography (EMG) for automatic detection of the aerobic and anaerobic thresholds during an incremental continuous cycling test using 1 min exercise periods in elite cyclists. (2) Methods: Sixteen well-trained cyclists completed an incremental exercise test (25 W/1 min) to exhaustion. Surface bipolar EMG signals were recorded from the vastus lateralis, vastus medialis, biceps femoris, and gluteus maximus, and the root mean square (RMS) were assessed. The multi-segment linear regression method was used to calculate the first and second EMG thresholds (EMGT1 and EMGT2). During the test, gas exchange data were collected to determine the first and second ventilatory thresholds (VT1 and VT2). (3) Results: Two breakpoints (thresholds) were identified in the RMS EMG vs. time curve for all muscles in 75% of participants. The two breakpoints, EMGT1 and EMGT2, were detected at around 70%-80% and 90%-95% of VO2MAX, respectively. No significant differences were found between the means of VT1 and EMGT1 for the vastii and biceps femoris muscles (p > 0.05). There were no significant differences between means of EMGT2 and VT2 (p > 0.05). (4) Conclusions: It is concluded that the multi-segment linear regression algorithm is a valid non-invasive method for analyzing the aerobic-anaerobic transition during incremental tests with 1 min stage durations